A rare case of bilateral Preiser’s disease originating from the distal pole of the scaphoid - Isgandarli, Shikhali; Çabukoğlu, Cengiz; Şensoy, Berk Özer (The European Research Journal, 2025)
The scaphoid bone – os naviculare manus – is an important bone in that it is located within the proximal row of carpal bones and articulates with both the radius and other carpal bones. Preiser’s disease is a rare entity and is commonly associated with avascular necrosis of the scaphoid without fracture or trauma. This case study describes a 55-year-old female patient who visited our outpatient clinic complaining of five months’ worth of pain and swelling on both of her wrists. The patient had no history of trauma or prolonged steroid use. The patient had pain around the thenar region and anatomical snuff box on both wrists. On a 2-directional wrist radiograph, the distal part of the scaphoid bone showed signs of subchondral sclerosis. Magnetic Resonance Imaging (MRI) was performed to verify the diagnosis. MRI of the patient’s wrist revealed bone edema at the distal pole of the scaphoid which was associated with Preiser’s disease. In this case study, we present a patient who had bilateral Preiser’s illness that began at the distal pole.